Kritik Atas Pemikiran Abdullahi Ahmed An-Naim Tentang Distorsi Syariah terhadap HAM - Sapiudin Sapiudin (AHKAM : Jurnal Ilmu Syariah, 2016)
In liberal studies, Sharia and human rights are two issues that are often opposed to distort the role of sharia in solving human right cases. In his writings on sharia and human rights issues, Abdullahi Ahmed an-Naim often applies rational rules as the source of truth and human values as a goal, but he excludes the role of Islamic law and its interpretation. Naim states that the human right problems in the world can not be solved by the sharia but can only be solved by secular laws. For example, the practice of slavery and discrimination against women and non-Muslims ethnic is a subjective conclusion that is counter productive to the role of sharia. Therefore, this conclusion is unacceptable and is necessary to have objective assessment. It is really clear that sharia is glorious and never distorts human rights at all.DOI: 10.15408/ajis.v16i1.2893